Segmental Spinal Myoclonus Complicating Lumbar Transforaminal Epidural Steroid Injection. Issue 5 (1st July 2018) - Wong, Stanley Sau Ching; Qiu, Qiu; Cheung, Chi Wai
Abstract : Objective: Lumbar transforaminal epidural steroid injection is commonly used for treating lumbar radicular pain. We report a case of segmental spinal myoclonus that developed during lumbar transforaminal epidural injection with local anesthetic and steroid. Case Report: A 58-year-old woman with failed back surgery syndrome presented with low back and right L3 and L4 radicular pain. As she had responded well previously to diagnostic selective nerve root injection with local anesthetic at the right L3 and L4 levels, lumbar transforaminal epidural steroid injection at the same levels was scheduled. During injection of ropivacaine and triamcinolone at the right L3–4 intervertebral foramen, she complained of back pain and immediately developed involuntary contraction of her right hip. The procedure was terminated. No new neurological deficit was detected when she was examined 15 minutes after the procedure. There were no abnormalities from blood tests and magnetic resonance imaging of the lower thoracic and lumbar spine. A neurologist subsequently made the clinical diagnosis of segmental spinal myoclonus. The myoclonus improved over 1 month and eventually resolved completely. Conclusions: Segmental spinal myoclonus is a rare complication after lumbar transforaminal epidural steroid and local anesthetic injection. Pain physicians should be aware of this potential complication.